Maternal serum apelin and YKL-40 levels in early and late-onset pre-eclampsia. (November 2014) - Kucur, Mine; Tuten, Abdullah; Oncul, Mahmut; Acikgoz, Abdullah Serdar; Yuksel, Mehmet Aytac; Imamoglu, Metehan; Balci Ekmekci, Ozlem; Yilmaz, Nevin; Madazli, Riza
<x xml:space="preserve">Abstract</x> Objective: The aim of the present study is to investigate whether alterations in the serum levels of apelin and YKL-40 differ between early and late onset pre-eclampsia and whether there is a correlation between apelin and YKL-40 in women who subsequently develop early and late pre-eclampsia. Materials and methods: A total number of 80 pregnant women, 40 with normal pregnancy and 40 with pre-eclampsia, were included in the present study. Both the normal pregnant and pre-eclamptic subjects were subdivided into two groups. Serum YKL-40 and apelin concentrations were measured. Results: Mean maternal serum YKL-40 levels were both lower in women who subsequently developed early (87.45 ± 3.07 versus 103.40 ± 4.29) or late (96.43 ± 4.06 versus 99.87 ± 3.63) pre-eclampsia than those who remained normotensive. The difference was significant in early-onset preeclamptic women (p < 0.05) rather than late-onset pre-eclamptic ones (p > 0.05). Mean maternal serum apelin levels were both higher in women who subsequently developed early (8.6 ± 3.6 versus 5.7 ± 1.2) or late (9.6 ± 2.5 versus 8.1 ± 1.8) pre-eclampsia than those who remained normotensive. The difference was significant in early-onset preeclamptic women (p < 0.05) rather than late-onset pre-eclamptic ones (p > 0.05). There was a significant negative correlation between serum apelin and YKL-40 levels (r = −0.48, p = 0.001). Conclusion: Circulating levels of apelin are significantly increased in early-onset pre-eclampsia, indicating the role of apelin in the discrimination of the early-onset of pre-eclampsia. On the other hand, maternal serum YKL-40 levels are not elavated significantly, indicating that adipose-derived apelin is primarily involved in the vascular pathogenesis of early-onset pre-eclampsia than macrophage-derived YKL-40.